(untitled) (Medical Forum Monthly, 2023)
Objective: Managing glycemic level in a surgical patient is critical. In this study we will manage the diabetes mellitus in patients presented for surgical disease. Study Design: Cross Sectional Study Place and Duration of Study: This study was conducted at the OPD Department of Medicine at PMCH Nawabshah from June 2016 to November 2017. Materials and Methods: 115 patients were enrolled for this study. 63 were male and 52 were female. Informed permission was taken from all the patients, study was done using proforma with history, clinical examination and investigations. All diabetic patients newly diagnosed and known case of Diabetes Mellitus with surgical disease were included for this study. Non diabetic with surgical disease and diabetic without surgical disease were excluded from this study. Results: 115 patients participated for this study, both male and female of all ages. All patients presented with surgical disease for surgery. Age range from 17-70 ys mean age 48.48+_10. HbA1C was from 5.60-10 mean 7.5+_0.78. Fasting Blood Sugar range 121-231 mg/dl mean 139.38+_22. Random Blood Sugar range 139-510 mg/dl mean 272.3+_67. All the patients were treated with insulin, on the day of surgery morning dose of insulin was omitted. Statical analysis was done using software SPSS 15 version. Conclusion: Uncontrolled Diabetes Mellitus is a major problem before Surgery and postoperative, by closed communication between physician, surgeon and anesthetic staff complications can be reduced. Good glycemic control before surgery and postoperative blood glucose control are important in reducing complications. Acid base balance and electrolyte status should be monitored for better surgery.